Kontribusi Abnormalitas Spermatozoa Terhadap Motilitas Spermatozoa Semen Beku Sapi Bali - Lumbantoruan, Risna F; Sumarsono, Teguh; Rosadi, Bayu (CV. SINAR HOWUHOWU, 2026)
This study aimed to determine the contribution of spermatozoa abnormalities to total motility and progressive motility in frozen Bali cattle (Bos javanicus) semen. The materials used consisted of 30 straws of frozen Bali cattle semen obtained from the Balai Besar Inseminasi Buatan (BBIB) Singosari. Analysis was carried out using Computer Assisted Sperm Analysis (CASA) to measure sperm motility and determine the levels of secondary and tertiary abnormalities. The data were analyzed using multiple linear regression with SPSS software. The results showed that no primary abnormalities were found in the observed samples. Secondary abnormalities had a negative and significant effect on total motility (p < 0.05), with a determination coefficient value of 62.5%, indicating that secondary and tertiary abnormalities together explained 62.5% of the variation in total motility. Secondary abnormalities had the largest effective contribution of 70% to the decrease in motility total. In contrast, tertiary abnormalities did not significantly affect either total motility or progressive motility. These results indicate that secondary abnormalities are the dominant factor influencing the decrease in the quality of Bali cattle frozen semen, particularly in terms of sperm motility. The conclusion of this study is that since no primary abnormalities were found, secondary abnormalities contribute to total motility, but not to progressive motility, and tertiary abnormalities do not contribute to either total or progressive motility in Bali cattle frozen semen.